2022
DOI: 10.1021/acsapm.2c01158
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobically Associated Functionalized CNT-Reinforced Double-Network Hydrogels as Advanced Flexible Strain Sensors

Abstract: Hydrogels have gained the attention of researchers worldwide and can be widely applied for use in medical technologies in human health and in industrial applications such as robotics. However, producing a hydrogel with proper mechanical properties, low hysteresis energy, quick shape recovery, and long-range strain sensitivity is still an ongoing development. More development into hydrogel technology could also lead to an increase in the effectiveness and lifespan of artificial joint replacements. Our hydrogels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The low energy dissipation implies good resilience of the hydrogel. 37 The Young's modulus of the hydrogel was 0.38 MPa when the compressive strain was 60% (Figure 2d). It also showed that as the number of loading− unloading cycles increased, there was a slight increase in Young's modulus.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The low energy dissipation implies good resilience of the hydrogel. 37 The Young's modulus of the hydrogel was 0.38 MPa when the compressive strain was 60% (Figure 2d). It also showed that as the number of loading− unloading cycles increased, there was a slight increase in Young's modulus.…”
Section: Resultsmentioning
confidence: 98%
“…Figure c reveals that there is less energy dissipated (maximum value of 1.5 kJ m –3 ) during the 100 loading–unloading cycles test at 60% compressive strain. The low energy dissipation implies good resilience of the hydrogel . The Young’s modulus of the hydrogel was 0.38 MPa when the compressive strain was 60% (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…First, nanocomposite hydrogel can detect a wide range of activities from body movements as motion sensors (Figure ). To characterize the sensitivity of the sensor, the gauge factor (GF) was introduced and calculated according to the equation GF = ( R–R 0 )/ R 0 /ε, where ε is the strain. , When the tensile strain is within the limit stretching range of the P­(AM-AC)-HC-NP3 hydrogel, the relative resistance varies linearly, and the GF reaches about 1.04 (Figure S10a). The response and recovery times of the sensors are shown in Figure S10b.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 These sensors can detect biological and mechanical activities and provide feedback through changes in their electrical output. 12 Over the years, a variety of dependable sensor materials have been developed, such as those utilizing carbon, 13−15 nanowires, 16 and conductive polymers. 17 However, a major obstacle faced by these sensors is their limited working range, large response time, and susceptibility to rapid conductivity deterioration under repeated large deformations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Flexible strain and electronic sensors have captured a great deal of attention due to their broad potential applications in areas such as electric skin, human movement detection, health monitoring, , and energy storage. , These sensors can detect biological and mechanical activities and provide feedback through changes in their electrical output . Over the years, a variety of dependable sensor materials have been developed, such as those utilizing carbon, nanowires, and conductive polymers .…”
Section: Introductionmentioning
confidence: 99%